Perhitungan Trafik dan Dimensi pada Jaringan CCS7 - Agung Dwi Prastowo; Sudjadi Sudjadi; Imam Santoso (Departemen Teknik Elektro, Universitas Diponegoro, 2012)
In any type of telecommunications network planning, calculate the traffic and the dimensions are always needed. Calculating the amount of carried out traffic to determine the traffic that will be distributed, while calculating the dimensions necessary to determine the amount of network that need to be provided. Similarly, in the CCS7 signaling network planning, traffic calculation and its dimensioning also needs to be done. In this paper will be discussed on how to calculate the dimensions of traffic and the CCS7 network. Objects that are calculated include the traffic between the SP and STP linkset, traffic between pairs of STP linkset, linkset dimensions, and dimensions of SP and STP.